Does Financial Development Benefit All? Insights from Indonesian Provincial Economies - Edi Nur Alamsyah; Jean-Claude Maswana (Journal of Developing Economies, 2026)
Objective: This study explores whether financial development benefits all regions equally by analyzing how the financial system influences economic growth across Indonesian provinces and examining the heterogeneity of this relationship across low- and high-income regions. Design/Methods/Approach: The study extends the Mankiw–Romer–Weil (MRW) growth framework by incorporating dynamic indicators of financial intermediation. Using a provincial panel dataset spanning 2010–2022, the analysis employs a two-step system GMM estimator to address potential endogeneity and capture growth persistence. Findings: Both real credit and deposit growth significantly enhance provincial economic performance; however, the benefits are unevenly distributed. The impact is markedly stronger in high-income provinces, where more advanced financial infrastructure amplifies the growth-enhancing role of finance. The findings remain robust across a range of sensitivity tests. Originality/Value: The study contributes novel subnational evidence on the finance–growth nexus within an emerging economy context. By introducing dynamic proxies of financial development within an extended MRW framework and explicitly accounting for regional income disparities, this study deepens the understanding of how financial systems shape uneven growth trajectories across provinces. Practical/Policy implication: The results underscore the need for region-specific financial policies. While high-income provinces would benefit from further market deepening and financial innovation, low-income regions require targeted interventions to enhance financial inclusion, literacy, and infrastructure, thereby fostering more inclusive and balanced economic development.